Sou uma cineasta!: Antônia Ágape e o cinema negro paraibano no feminino - Ferreira, Carine Fiúza (2024)
This dissertation, developed from an antiracist and Afrocentric perspective, aims to outline the historiographical contours of Paraibano Black Cinema. Based on a preliminary diagnosis of the state of the art regarding the representation of Black bodies in Paraibano cinematography from 1918 to 2023, the research takes a leap to question representativity—where are Black professionals in space/time?—with the aim of highlighting the systemic inequalities and barriers that still persist, limiting opportunities and contributions to the establishment of Black Cinema. This dissertation contributes to a broad and updated view of the presence of Black people in Paraibano cinema, inevitably addressing its absences and silences. To achieve this, it draws a parallel between the landmark established by the documentary Aruanda (Linduarte Noronha, 1960)—the first Paraibano film featuring Black people—and the overlooked milestone of As Cegas (Maria Antônia Pereira Ágape, 1982)—the first film made by a Black person, which is recognized in this research as pioneering in Paraibano Black Cinema, adhering to criteria that articulate representation, representativity, and a careful intersection between the two. Two methodological approaches were chosen to address what has been silenced by historical records and to create a map of memories oriented toward a counter-hegemonic perspective: a cartography that combines a detailed documentary review with the reformulation of narratives about Black filmmakers; and an "escrevivência", based on the life experiences and encounters between two filmmakers: Carine Fiúza (the author of this dissertation and audiovisual creator) and Maria Antônia Pereira, also known as Antônia Ágape (the first Black female filmmaker in the state). In dialogue with Antônia Ágape, this text seeks to reaffirm the role of the creative self as an expression of autonomy, desire, and potency, thereby transcending limitations imposed by hegemonic narratives. It aims to construct Black female narratives that actively challenge dominant discourses in order to interweave diverse forms of knowledge.